2007
DOI: 10.1021/ar700088f
|View full text |Cite
|
Sign up to set email alerts
|

Cinchona-Modified Platinum Catalysts: From Ligand Acceleration to Technical Processes

Abstract: This Account records work carried out in our laboratories during the last 2 decades in the field of enantioselective heterogeneous hydrogenation. Of particular interest was Orito's catalytic system, platinum catalysts modified with cinchona alkaloids for the hydrogenation of activated ketones. Described are the development of the optimal platinum catalyst and modifier and the expansion of the scope of the catalyst. Kinetic studies aimed at understanding the mode of action of the catalyst revealed that the cinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
143
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 48 publications
5
143
1
2
Order By: Relevance
“…A review of the reports published in the past few years on the enantioselective hydrogenation of activated ketones over Pt catalyst modified by cinchona alkaloids (the Orito reaction) reveals that all (or most) that can be found out about the reaction on Pt-CD using the currently available experimental methods is already known (see summarized since 2006 in [8][9][10][11][12][13]). The results achieved are hallmarked by the extension of the scope of the reaction and by the deeper understanding of the reaction mechanism in general and that of chiral induction in particular: (1) ee values over 90% are already attainable in the hydrogenation of certain substrates [14][15][16][17][18][19][20][21]; (2) the success of studies on the reaction mechanism has been made possible by the application of a great variety of instrumental techniques (see summarized in references [22][23][24][25][26][27][28][29][30][31]; however, studies similar to those performed on Pt-CD should also be repeated on Pt-CN, Pt-QN and Pt-QD catalysts).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the reports published in the past few years on the enantioselective hydrogenation of activated ketones over Pt catalyst modified by cinchona alkaloids (the Orito reaction) reveals that all (or most) that can be found out about the reaction on Pt-CD using the currently available experimental methods is already known (see summarized since 2006 in [8][9][10][11][12][13]). The results achieved are hallmarked by the extension of the scope of the reaction and by the deeper understanding of the reaction mechanism in general and that of chiral induction in particular: (1) ee values over 90% are already attainable in the hydrogenation of certain substrates [14][15][16][17][18][19][20][21]; (2) the success of studies on the reaction mechanism has been made possible by the application of a great variety of instrumental techniques (see summarized in references [22][23][24][25][26][27][28][29][30][31]; however, studies similar to those performed on Pt-CD should also be repeated on Pt-CN, Pt-QN and Pt-QD catalysts).…”
Section: Introductionmentioning
confidence: 99%
“…23-138 25 The key mechanistic question, of course, concerns the nature of the surface-mediated molecular 139 events that result in enantioselectivity and much effort has been expended in addressing this crucial 140 issue, including extensive and detailed studies of the effect of reaction variables on enantiomeric7 excess. 8,26 The original reaction reported by Orito 7 gave up to 92% yield with 81.9% optical yield with 142 the best substrate, modifier, solvent combination, although subsequent optimization has shown it is 143 possible to get high enantiomeric excesses (> 90%) even in a flow reactor operating at relatively high 144 turn-over frequencies (84000 h -1 ). 27 …”
mentioning
confidence: 99%
“…2, 2010 Supported platinum catalysts have been widely studied for this type of application. 29 It has been found that metal particle size plays an important role in asymmetric synthesis when performed in the presence of cinchonidine as a chiral inducer. Metal crystals around 3.0 nm obtained with catalysts having metal loading close to 5 wt.% have led to the most promising catalytic behaviour.…”
mentioning
confidence: 99%